A New Royal Library at the Waterfront, Copenhagen - Dagmar Richter (Oz, 1994)
To copy in an architectural design process is an act of unconscious appropriation which goes on continually at nearly any designers desk. A borrowed quotation from Rosalind Krauss clarifies what I mean…